Revisiting the interplay between contractual and relational governance: A qualitative and meta‐analytic investigation. Issue 1 (2nd October 2014) - Cao, Zhi; Lumineau, Fabrice
Abstract: Although extant literature has shown that formal contracts and relational governance play a key role in interorganizational relationships, the nature of their interplay still remains equivocal. To better understand the relationships between contractual and relational governance, we conducted a qualitative review and meta‐analysis of the existing literature. Meta‐analytic results from 33, 051 interorganizational relationships across 149 empirical studies have indicated that contractual governance is positively related to both sides of relational governance—trust and relational norms. Our results have also indicated that contracts, trust, and relational norms jointly improve satisfaction and relationship performance and jointly reduce opportunism. These findings provide strong evidence for the complementarity arguments of the contractual–relational governance relationships and their joint impacts on performance. We also found that the mutual relationships between contractual and relational governance are moderated by the institutional environments, the interorganizational relationship type and length, and the construct measurement of contracts. Overall, this study provides new insights on when contractual and relational governance complement or substitute each other. We discuss the implications of our study for theory and practice and propose a research agenda for future research on governance in interorganizational relationships.